871 AN ADVANCED BREATHING DISORDER IN HEART FAILURE: IS THERE AN OVERLAP THROUGH EXERCISE OSCILLATORY VENTILATION AND CHEYNE-STOKES RESPIRATION? A CASE REPORT. (15th December 2022) - Baracchini, Nikita; De Martino, Fabiana; Cunha, Goncalo; Carriere, Cosimo; Merlo, Marco; Agostoni, Piergiuseppe; Sinagra, Gianfranco
Abstract: Case summary: A 60-year-old man, normal-weighted, former smoker with a known non obstructive hypertrophic cardiomyopathy (HCM), severe mitral and tricuspid regurgitation and permanent atrial fibrillation was hospitalized for decompensated heart failure (recent worsening of exertional dyspnoea and appearance of lower limbs oedema). At the admission the ECG documented a permanent AF with normal average heart rate (66 rpm). Blood tests showed only a mildly elevation of BNP (497 pg/ml). Before the valvular repair surgery patient completed the diagnostic work-up with spirometry and cardiopulmonary exercise testing (CPET). The spirometry showed a mixed disorder predominantly obstructive (FEV1 1.8 L/min, 51% of predicted value), consistent with COPD. Also DLCO was moderately reduced. CPET documented a severe reduction in functional capacity (VO2 peak/Kg 9.2 ml/Kg/min, 32% of predicted value, Watt at peak 61), clear signs of cardiac and pulmonary vascular limitation (VO2 Work Slope 7.1, VE/VCO2 Slope 45). Interestingly, during the entire duration of the effort there were an exercise oscillatory ventilation (EOV). Instead, cardiopulmonary registration at rest showed an advanced oscillatory breathing disorder with regular long phases of apnea (average duration of 40 sec). Apnea phases were diurnal and were associated with desaturation at pulsossimetry (SpO2 93-92%). This rest breathing disorder consisted with the definition of Cheyne-Stokes respiration. Of note, the patient had no previous history of OSAS or central sleeping disorder. Discussion: Cheyne-Stokes respiration (CSR) is historically considered as a central sleeping disorder, particularly common in patients with heart failure with reduced ejection fraction (HFrEF) with a wide prevalence range between 16% up to 50%. It is also well known its negative prognostic value as it highly impairs quality of life and increases cardiac mortality. Recently, in HFrEF patients emerged that CSR could be also diurnal and sometimes associated to EOV. The peculiarity of this clinical case lies firstly in the fact that we clearly documented a possible overlap through EOV and CSR, respectively seen as exerctional and rest advanced breathing disorders. Secondly, CSR was previously reported predominantly in case of LVEF < 40%, but this patient had a non obstructive HCM without systolic disfunction (LVEF was 63%). This suggest that CSR and EOV could have the same pathophysiology pathway, with a continuum through each other, regardless the model of HF (reduced vs preserved ejection fraction). Keywords: Cardiopulmonary Exercise Testing, Exercise Oscillatory Ventilation, Cheyne-Stokes Breathing, Heart Failure, Hypertrophic Cardiomyopathy.